Manajemen Pemasaran Politik Partai Kebangkitan Bangsa Dalam Persiapan Pemilu 2024 di Sumatera Utara - Kamaluddin Kamaluddin; Winni Saiyudina; Syifa Inayah; Ade Syafrian Pratama Lahagu; Muhammad Fariz (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
Political marketing is a process in which prospective leaders will introduce themselves and offer work programs or their future visions and missions if they take office to the wider community who are the target of their political marketing process. The purpose of this political marketing is to attract the public's interest in voting. candidates to win elections and become leaders in certain areas. The target market in political marketing is the acquisition of the most votes by political parties through mass choice in general elections. This journal will discuss the management of political marketing that will be carried out by the Partai Kebangkitan Bangsa (PKB) in preparation for the upcoming 2024 elections. The method used in writing this journal is a mixed descriptive method (qualitative and quantitative). The purpose of writing this journal is so that writers and readers can broaden their horizons and take many lessons from various political marketing management strategies carried out by the Partai Kebangkitan Bangsa in preparing for success in the democratic party in 2024. The results found are that political parties, especially PKB, are obliged to maintain transparency, honesty, openness, and freedom in the implementation of elections. To maintain this commitment, the party would always train and thoroughly prepare all personnel so that they could carry out their duties effectively as witnesses to oversee vote counting up to the national level. We hope that the preparation of this journal can provide benefits and additional insight regarding the management of political marketing in a political party for all those who read it. Key Words: Management, Political Marketing, Political Parties, Elections.